Pengaruh Penggunaan Laba dan Arus Kas Terhadap Kinerja Keuangan Bank Swasta Indonesia Yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2016 – 2018 - Sinurat, Mangasi; Ilham, Rico Nur; Sari, Lira Mustika (Accounting Progress, 2023)
This study aims to find out how the Effect of Use of Profits and Cash Flow on the Finance of Indonesian Private Banks Listed on the Indonesian Stock Exchange. The research method used is quantitative data method. While the data used is secondary data. The method of data analysis in this study uses multiple linear regression analysis to obtain a comprehensive picture of the effect of the use of profit on financial performance. To find out whether there is a significant effect of the independent variable on the dependent variable, a simple linear regression model is used. The results of testing the hypothesis using simple regression analysis and t test show that the Use of Profits has a positive and significant effect on the Financial Performance of Indonesian Private Banks Listed on the Indonesia Stock Exchange.